Crecimiento postnatal y desarrollo del vuelo en el murciélago Leptonycteris yerbabuenae en Chiapas, México - Martínez-Coronel, Matías; Cervantes, Fernando A.; Hortelano-Moncada, Yolanda (THERYA, 2014)
Introduction: Neonate bats represent 12-43% of postpartum-maternal body mass, but unlike other small mammals with large offsprings, bats are altricial and totally dependent on maternal care for survival. Neonates of several bat species are born naked, with low thermoregulatory ability; therefore their growth and development are affected by factors such as humidity and temperature, likewise by sex and food availability, among others. Phyllostomidae is the most diverse family of bats in the Neotropics, nevertheless, there are few studies on the postnatal growth and development of their offspring and especially of glosophagine bats. For that reason, we described the postnatal growth and development of a population of Leptonycteris yerbabuenae inhabiting â€œThe Laguitosâ€ Cave, in the state of Chiapas, México. This species is distributed from the southern United States, through most of Mexico to Guatemala and El Salvador .In Mexico this species is listed as â€œthreatenedâ€ by the Mexican government (SEMARNAT, 2010). Methods: Based on capture-recapture data, we examined the growth trajectories of three morphological variables and flight development of young Leptonycteris yerbabuenae during 1998 and 2001. Sexual variation, and inter-year variation among specimens of the same age category was assessed by a t Student test. The growth of each variable was measured with a lineal regression analysis, meanwhile the growth parameters were derived from a logistic growth equation and from a polynomial model. To describe the flight development in young bats, we classified these as non-volant, semivolant and volant as was done by Stern et al. (1997) inPhyllostomus hastatus. Results: The highest records for ambient and roost temperature were in 2001, and so were the lowest records for relative humidity compared with 1998 conditions (Fig. 1). Male and female young bats (Fig. 2) were morphologically similar in the three variables assessed in both years (Table 1). The body mass and length of the forearm increased linearly the first three weeks in both years, while the length of the epiphysis grew until the second week in 1998 and day 10 in 2001, then the growth rate decreased in all variables (Figure 3, Table 2). The sustained flight was achieved at ages 15 and 20 days in 2001 and 1998, respectively (Table 3). Discussion and conclusions: This study shows that neonates of Leptonycteris yerbabuenae from Chiapas born naked and with the ear meatus closed compared with those of Carbo, Sonora (Gould 1975), what reveals intraspecific variability of these traits. The morphological similarity between male and females young bats was expected; because there is not secondary sexual dimorphism in adults. Neonates of 1998 had lesser body mass and greater length of the fourth metacarpal-phalangeal epiphyseal gap than specimens of 2001. Differences between years were persistent during growth phase, and maybe these results were consequences of different weather conditions that prevailed in each year. The growth parameters derived from the logistic model for forearm length (0.07-0.10) and body mass (0.06-0.10) of L. yerbabuenae were similar to other neotropical phyllostomid bats, but lower than vespertilionid bats. These results may be influenced by phylogenetic distance or by environmental conditions. The sustained flight started five days earlier in 2001 compared with 1998, probably influenced by different environmental conditions that prevailed each year. Therefore the sustained flight was achieved at an age similar to those of other phyllostomid bats. Key words: Cave, Chiroptera, Phyllostomidae, relative humidity, temperature, growth trajectories.